External Parasites of Acanthopagrus Latus in Bahr Al-Najaf, Iraq: Parasit Eksternal Acanthopagrus Latus di Bahr Al-Najaf, Irak - Kareef, Haki Abdulabas Issa (Indonesian Journal on Health Science and Medicine, 2025)
Abstract. 112 shank fish (Acamthopagruslatus) from Bahr Al-Najaf water in ALNajaf province were examined. 15.1% was the overall percentage of external parasite infection and intensity. Tetrahymenapyriformis infection rate was 3.5%, Chloromyxumdubinm infection rate was 12.5% with intensity 4.0, Argulus foliacus infection rate was 14.2% with intensity 3.4, and Ergassilusmosulens 9.8% with intensity 4.2. The percentage of infections with the parasites under investigation varied by month.   Highlights: Parasite Diversity: Four external parasite species were identified in Acanthopagrus latus, affecting different body parts. Monthly Variations: Infection rates fluctuated across months, with environmental factors likely influencing prevalence. Statistical Analysis: No significant monthly differences in infection rates were found, suggesting stable environmental or host-parasite dynamics.